Key concepts in tourism research - Botterill, David; Platenkamp, Vincent; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2012)
This book walks students through the selection and application of research methods within tourism. Experienced authors introduce the relevant language and theory of key methodologies and then develop them using strategic literature review and the inclusion of international examples which relate directly to tourism.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Tourism -- Research -- Methodology; Electronic books